Broader outcomes in procurement policy – a case of New Zealand pragmatism. Issue 3 (14th August 2021) - Allen, Barbara
Abstract : Purpose: The purpose of this paper is to investigate how the underpinning ideas of public procurement allowed for broader outcomes – a more strategic form of public procurement – to emerge. The paper contributes to the literature on public procurement by empirically addressing the evolution of procurement as a government policy lever in New Zealand so as to demonstrate how policy pragmatism can ensure a shift without a complete overhaul of a complex system. Design/methodology/approach: The paper has used a single country case study to examine a recent development in procurement policy. The objectives of the paper are achieved by adopting a unique conceptual framework connecting ideas, sensemaking and bricolage. Findings: The paper provides empirical and conceptual insights about how bricolage, or policy pragmatism, aids in dealing with the constraints of ideational legacies. It demonstrates a particular form of targeting in procurement, common in public administration but not well understood in the procurement field. Research limitations/implications: Single country case studies lack scientific generalizability. However, they add to the canon of knowledge that is lacking in the field of public procurement in this case. They also provide a stronger starting point for further research especially with respect to comparative studies. Practical implications: The paper provides an excellent example of the development of procurement policy that is useful for procurement officials from other countries undergoing change or looking to update or create procurement policies. It shows a high-level process of implementation for government priority outcomes from a country well-known for its quality of public management and governance. Social implications: New Zealand has significant equity issues especially as related to its indigenous population. Procurement is being used increasingly as a lever to improve equity. This article includes information about New Zealand's uptake of social procurement. Originality/value: This paper fulfils a need for greater understanding of how policy is "put together" and the dynamics at major points of change or the implications of policy changes. To the best of the author's knowledge, this case study of procurement policy in New Zealand is original, and the author is aware of no other similar work emanating from New Zealand in the academic journals.